The sanitation access to developing Asia: India's performance over 2001 and 2011. Issue 2 (27th May 2014) - Hossain, Moazzem; Howard, Paul
Abstract : Purpose: – The purpose of this paper is to shed light on India's performance in sanitation over the last decade as it strives to meet the Millennium Development Goal target. Design/methodology/approach: – In doing so, both qualitative and quantitative analyses are employed. The latter method includes a regression analysis. Income and income inequality variables have been included in the analysis. Findings: – Whilst India has made progress towards achieving access to sanitation for its people, the nation continues to perform relatively poorly to its neighbours and on a comparative global basis. At the national level, substantial rural-urban and income disparities are linked to a reduced level of sanitation access. Both forms of analysis support the view that income inequality in India is directly related to a lack of sanitation facilities. Research limitations/implications: – The study is based on secondary data gathered from WHO and UNICEF sources. These are national data gathered by these agencies in two periods. These are aggregated data. Practical implications: – The study has major practical implications in policy formation in the area of sanitation access to both rural and urban India. The state level data analysed by the study will also be useful to make policies at disaggregated level. India, indeed, needs to improve the conditions on an urgent basis. Even in South Asia standard, this nation is behind from almost all other nations of the region. Social implications: – The social implications are to make people particularly poor aware about the sanitation issue lack of which contributes to health hazards and gestro condition for children and old. The sanitation related diseases contribute to huge loss of working hours in both rural and urban communities. Originality/value: – The study contributes original ideas and demonstrates with a simple regression analysis how sanitation depends on income and income inequality of the poor.